Το κίνημα ανεξαρτησίας του Πόντου και οι αυτόνομες Ελληνικές περιοχές στη Σοβιετική Ένωση του μεσοπολέμου - Αγτζίδης Βλάσης (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1992)
Economic circumstances since the mid-nineteenth century, favoured the rapid development of Pontic Greek society and culture on the Northern littoral of Asia Minor and its immediate hinterland. The Pontic Greek merchants managed to achieve a leading role in the economic life of the Black Sea region. This development ran parallel to similar phenomena in the Greek communities on the Russian coast of the Black Sea and in the interior of Transcaucasia. The end of the period of Pontic development coincides with the First World War. As a reaction to Ottoman policies threatening their security and survival, the Pontic Greeks resorted to the formation of an organisation for dynamic resistance. In every region of Pontos, secret resistance groups were established. The same phenomenon is observable among the Greek communities of Southern Russia. The main objective of these groups was the creation of an independent republic based on the Pontic territories of the Ottoman Empire. The October Revolution in Russia changed completely the scene by bringing to power a government friendly towards Turkish interests. Following the defeat of the Central Powers in World War I, the hopes of the Pontic Greeks were rekindled. The two interdependent objectives, the creation of an independent republic in the Pontos and the achievement of autonomy in the territory of the former Russian Empire for local Greek populations, set in motion a large scale Pontic political movement. The defeat of the Greek army in Asia Minor in 1922 however and the Lausanne Treaty of 1923 sealed the fate of the Pontic movement in Turkey. Greek rebels nevertheless continued to fight for their cause on the Pontic mountains for a year after Lausanne. Those who survived sought refuge in the new Soviet Union. In the multinational Soviet Union the Pontic movement focused on the achievement of cultural and educational rights. A short movement for autonomy that surfaced at the end of the 1920s was difinitively defeated in 1937 in the context of the broader Stalinist policies of the period.